Silat-AI: Transforming silat gayong training with AI-enhanced pose detection / Ahmad Suffian Muhammad Shahril ... [et al.] - Muhammad Shahril, Ahmad Suffian; Isawasan, Pradeep; Song Quan, Ong; Ahmad Salleh, Khairulliza (2024)
The Silat-AI innovatively applies artificial intelligence (AI) to enhance the training of Silat Gayong, a traditional Malaysian martial art. This web-based system uses a camera to capture and analyze practitioners' movements in real time. By employing machine learning models, specifically Random Forest, the system achieves high accuracy in recognizing and classifying martial arts techniques. This not only modernizes the learning experience but also makes Silat training more accessible and appealing to today's learners, blending traditional practices with modern technology.